El tamizaje bucal: fundamentos y presentación de una experiencia - Tamayo-L., Aicardo (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This article presents a screening test for the early identification of many buccal pathologies. The concept, the components, the characteristics, the advantages and disadvantages of the method are presented. and the results of their application are analyzed in practice. The precise indexes of dental caries in the population are not known due to the difficulty of carrying out massive and periodic studies, but it is inferred that their incidence is increasing because the school population is not attending the health centers, according to recent reports of dental institutions responsible for public health in Antioquia. The screening test is a strategy that allows the detection of risk’s factors and the early diagnosis of diseases since the early asymptomatic phase. With the buccal screening the demand is induced to the health centers detecting oral pathologies in the early stages in big populations of children and adolescents. One can also achieve a presumptive diagnosis of buccal health that provides information that would permit establish the prevalence of the problem and a program of preventive treatment. In the municipality of Envigado - Antioquia 10.489 children of the public schools were screened with a minimum of costs, complexity and delays and with good acceptance of the community. The affected children were referred to their respective health services by means of referrals to family parents and teachers. The buccal screening should be done periodically with the purpose of making epidemiologic surveillance to frequent problems such as dental caries.